Material concreto para el desarrollo de destrezas con criterio de desempeño del bloque curricular numérico en los estudiantes de octavo año de educación general básica, del colegio fiscal mixto Hernán Gallardo Moscoso de la ciudad de Loja, periodo lectivo 2012 – 2013. Propuesta alternativa - Romero Aguilar, Bélgica Johanna (2014)
This research includes a study on the particular material for the development of skills with performance criteria Curricular Num Lock in our eighth year of the Attorney General Basic Education College Joint Hernan Moscoso Gallardo semester 2012-2013. The objectives that guided the research are: • Analyze how the teacher has knowledge about the specific material influence the development of skills with performance criteria Curricular Num Lock in our eighth year of Basic General Education College Joint Fiscal Gallardo Hernan Moscoso. • Establish how the use of concrete material impact on the development of skills with performance criteria Curricular Num Lock in our eighth year of Basic Education College Joint Fiscal Gallardo Hernan Moscoso. The results of field research stands out, the teacher uses the abacus as concrete material, the fractional cake and mathematics letters because they are of great help in rendering operations on the number line. The teacher despite having a clear concept on specific materials are not used in a proper way, because he uses are poorly applicable representations on straight as in the case of mathematics letters, but if the basic operations and when using these materials provide students with a greater understanding in the topics being something beneficial because ultimately helps them develop skills with performance criteria. The results of the survey of students that stresses that the teacher uses as concrete material strips, and the lowest percentage taptana the multibase blocks and mathematical charts. Moreover, in the survey of teachers stated that he only uses the abacus, the fractional cake and mathematical charts. Determining that the specific teaching materials used are appropriate because it allows the student to manipulate and thus develop skills to achieve performance criteria specifically in Curriculum Num Lock.